Morpholine-mediated defluorinative cycloaddition of gem-difluoroalkenes and organic azides - Huang, Tzu-Yu; Djugovski, Mario; Adhikari, Sweta; Manning, Destinee L.; Roy, Sudeshna (Beilstein Journal of Organic Chemistry, 2023)
Here, we report the first transition-metal-free defluorinative cycloaddition of gem-difluoroalkenes with organic azides in morpholine as a solvent to construct fully decorated morpholine-substituted 1,2,3-triazoles. Mechanistic studies revealed the formation of an addition–elimination intermediate of morpholine and gem-difluoroalkenes prior to the triazolization reaction via two plausible pathways. Attractive elements include the regioselective and straightforward direct synthesis of fully substituted 1,2,3-triazoles, which are otherwise difficult to access, from readily available starting materials.
Keywords: [3 + 2] cycloaddition; defluorination; fully decorated 1,2,3-triazoles; gem-difluoroalkenes; organic azides